Examining the Emotional Tone of Student Evaluations of Teaching - Newman, Derek (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2025)
Student-written evaluation (N = 600) of professors was examined to determine the emotional tone of the words used to evaluate faculty. Using the revised Dictionary of Affect (DOA; Whissell, 2009), evaluation words (N = 26,764) uploaded to the Rate My Professors website between 2018 and October of 2023 were measured for their pleasantness, activation, and imagery. Overall, the emotional tone of the students’ written evaluation was very close to the DOA’s definition of everyday English (M = 50) for all three categories: pleasantness (M = 51.1, SD = 6.3), activation (M = 52.2, SD = 4.8), and imagery (M = 50.2, SD = 7.4). The results indicated that the written evaluations were uniform in expression and emotional tone: neither very pleasant/unpleasant, active/passive, or imagery/abstract. While significant relationships were found with professor quality and difficulty ratings, the number of words in the evaluation, and the instructor’s gender, all associations had small correlational strengths and weak effect sizes, indicating that the variables might not be strong predictors of the emotional tone of student evaluations. If student written evaluations are not emotionally charged, then there is an opportunity to reduce any negative feelings faculty members have attached to the process.